Retinal nerve fibre layer changes in optic neuritis in Indian population - Anand Ravikumar; Mukundhan Muraleedharan; Kasthuribai Hariharasubramanian; Sameer Chaudhary; Kowsalya Akkayasamy (TNOA Journal of Ophthalmic Science and Research, 2022)
Context: Retinal nerve fibre layer (RNFL) loss associated with optic neuritis has been documented in western literature. However, only one study documents the same in Indian eyes. The RNFL thickness varies from in different populations, and several genetic and environmental factors may have an impact on RNFL changes. Aims: To evaluate retinal nerve fibre layer changes using spectral domain optical coherence tomography associated with optic neuritis in Indian population. Settings and Design: This was a cross-sectional observational study conducted at a tertiary eye care hospital in India, in the department of Neuro Ophthalmology. Methods and Material: This was a cross-sectional observational study which included 20 patients who were diagnosed to have optic neuritis, three months to one year prior. SDOCT was done to measure RNFL thickness and the same was compared with fellow unaffected eyes and normative database. Results: Average RNFL thickness of unilaterally affected eye (80.77 ± 25.59 μm), was significantly reduced when compared to the unaffected eye (97.92 ± 24.46 μm) (P = 0.031) and the normative data of device (98 ± 1.0 μm) (P = 0.031). Average RNFL thickness of bilaterally affected eyes was (67.71 ± 27.09 μm), and significantly reduced when compared with the normative data (98.43 ± 0.76μm) (P < 0.001). Conclusions: An overall significant reduction in the RNFL thickness was observed in the affected eyes when compared to the fellow unaffected eyes and the normative database. This reduction was most pronounced in the temporal quadrant indicating the affliction of the papillomacular bundle.